INTEGRATING COGNITIVE, COMMUNICATIVE, AND GAME-BASED APPROACHES IN TEACHING EFL LEARNERS - Madinabonu Abdullayeva (Bright Mind Publishing, 2025)
This article describes an integrated methodology for teaching English as a foreign language (EFL) that combines cognitive, communicative, and game-based approaches to improve students' language and communication skills. This study draws on constructivist theory, communication principles, and motivational frameworks to demonstrate how interactive and experiential teaching methods can be adapted to secondary and tertiary EFL learners. This study highlights the effectiveness of game-based methods, authentic communication, and social interaction in developing fluency, learner autonomy, and intercultural awareness.
Keywords: EFL teaching, communicative competence, constructivism, cognitive development, game-based learning, learner autonomy, interactive methodology.